Diabetic ketoacidosis, cerebral venous sinus thrombosis and fulminant cerebral oedema in COVID-19 infection complicated by Klebsiella pneumoniae infection. Issue 4 (4th April 2022) - Wallace, Lindsey A; Hocker, Sara E; Dubrock, Hilary; Bauer, Philippe
Abstract : We present an unusual case of a woman in her 30s who was admitted for diabetic ketoacidosis (DKA) in the setting of newly diagnosed but late COVID-19 infection with associated Klebsiella pneumoniae infection. Her altered mental status, out of proportion with her metabolic decompensation, revealed a superimposed cerebral venous sinus thrombosis (CVST) with fulminant cerebral oedema and ultimately brain death. This unusual and fulminant case of cerebral oedema in the setting of COVID-19 infection with bacterial infection, DKA and CVST was the perfect storm with multiple interwoven factors. It offered diagnostic and treatment challenges with an unfortunate outcome. This unique case is a reminder that it is important to consider a broad neurological differential in patients with COVID-19 with unexplained neurological manifestations, which may require specific neurointensive care management.